ANALISIS DEBIT BANJIR RENCANA BENDUNG TRITIS KABUPATEN SRAGEN - Sari, Lidya Ayu Setya Kumala; Wijayanti, Paska; Priyanto, Kusdiman Joko (Jurnal Teknik Sipil dan Arsitektur, 2025)
Water availability is an aspect that should be given high priority by the government to meet community needs, both in urban and rural areas. Generally, the current water sources come from rivers, canals, or shallow groundwater wells. The water availability in irrigated land obtained from weirs is crucial for the agricultural sector. Dams have a role to hold water and distribute it through irrigation channels to agricultural land, in order to ensure consistent water availability, especially in the dry season. Tritis Dam functions to raise the elevation of the river water level so that it can be used to irrigate into irrigation channels. Tritis weir is a permanent dam with a stone masonry structure located in Sambirejo Village, Sambirejo District, Sragen Regency, which is located in the Tritis Watershed with an area of ??31.15 km2. The purpose of this study is to determine planned flood discharge value. The method used in this study is the Synthetic Unit Hydrograph (HSS) ITB-I, but previously it must process GPM (Global Precipitation Measurement) satellite rainfall data and calculate the planned rainfall using the Log Pearson III frequency distribution method. The planned flood discharge in the Tritis Watershed, Sragen Regency using the HSS ITB I method was obtained at 258.41 m3/second for a 50-year return period and 318.09 m3/second for a 100-year return period.